Meningkatkan Hasil Belajar Operasi Hitung Bilangan Pecahan dengan Kartu Bilangan Siswa Kelas VI SDN 3 Mangliawan Kecamatan Pakis Kabupaten Malang - Wardani Harahap, Annisa; Hasanah Hutagalung, Rodiah; Azizah Harahap, Nur; Sofiyah, Khotna (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Improving mathematics learning outcomes is one of the important goals that students are expected to achieve in mathematics learning, but in reality most students still have difficulty understanding the fractional arithmetic operations they are learning. This study aims to improve the learning outcomes of fractional arithmetic operations through number cards. The type of research is classroom action research with all grade VI students of SDN 3 Mangliawan, Pakis Kabutane District, Malang, 2019/2020 academic year as research subjects. This research is said to be successful if it meets the success indicators, namely: (1) the average value of students' fractional arithmetic learning outcomes increases and meets the minimum completion criteria of 75; and (2) the percentage of students who complete it increases and reaches ≥ 75% of the total number of students. The results of the study showed that: (1) in Cycle I the average assignment score was 69.19 and the percentage of students who completed it was 45.16, (2) while in Cycle II the average assignment score was 84.68 and the percentage of students who completed it was 90.32, and (3) there was an increase in the average assignment score from Cycle I to Cycle II of 15.49 or 22.39% and there was an increase in the test score from Cycle I to Cycle II of 14.52 or 21.80%. The conclusion obtained is that the application of the number card method can improve the learning outcomes of fractional number arithmetic operations of Class VI students of SDN 3 Mangliawan, Pakis District, Malang Regency in the 2019/2020 academic year. For teachers who teach Mathematics in elementary schools, it is necessary to use learning media that are appropriate to the material being discussed, so that the learning atmosphere for Mathematics is not in a tense atmosphere but instead in a pleasant atmosphere.